Relationships between vitamin A and PCBs in grey seal mothers and pups during lactation - Vanden Berghe, Marie; Mat, Audrey; Arriola, Aline; Polain, Stephanie; Stekke, Valerie; Thome, Jean-Pierre; Gaspart, Frederic; Pomeroy, Patrick; Larondelle, Yvan; Debier, Cathy (Environmental Pollution, 2010)
A previous study has shown a simultaneous increase of vitamin A and PCBs in grey seal (Halichoerus grypus) milk at late lactation (Debier et al., 2004). Here we sought to understand this unexpected relationship by comparing the dynamics of vitamin A and PCBs in the different tissue compartments of transfer. Lactating grey seals and their pups were sampled longitudinally in Scotland during the 2006 breeding season. As blubber reserves decreased, concentrations of vitamin A and PCBs increased during lactation in the inner layer of maternal blubber. A concomitant rise was observed in milk and consequently in the serum of suckling pups. The similar dynamics of vitamin A and PCBs in milk and inner blubber suggest a common mechanism of mobilisation from maternal body stores and transfer into the milk. A panel data analysis highlighted a negative impact of PCBs in milk and pup serum on vitamin A status in pup serum. (C) 2009 Elsevier Ltd. All rights reserved.